Manganese-modulated proteome and phosphoproteome dataset in the opportunistic yeast Candida albicansPRIDE - Manon Henry; Michael Woods; Davier Gutierrez-Gongora; Jennifer Geddes-McAlister; Adnane Sellam (Data in Brief, 2025)
The ability of the opportunistic yeast Candida albicans to acquire and maintain homeostatic levels of manganese (Mn), particularly in the metal-limited host environment, is an important determinant of its fitness. Although significant focus has been given to mechanisms of iron and copper acquisition and their roles in C. albicans fitness, little is known about how this yeast maintains and controls Mn homeostasis. Here, we present a comparative proteomic and phosphoproteomic analysis in C. albicans cells experiencing Mn starvation. Both proteome and phosphoproteome of the C. albicans reference strain SC5314 grown in Mn-deplete medium were compared to those of cells thriving in Mn-replete medium. Samples were collected in three biological replicates at two time-points (5 and 90 min). Mass spectrometry-based proteomics identified approximately 1500 proteins and over 140 phosphorylated proteins. Proteomic data were analyzed using MaxQuant and Perseus, and all datasets were deposited in the PRIDE repository (accession number PXD064206). Gene ontology analysis was performed to characterize biological processes and signaling pathways affected by Mn availability. This dataset provides a resource for studying Mn homeostasis and regulatory phosphorylation in fungal pathogens. The dataset can be reused for comparative analysis with other fungal species or stress conditions involving transition metal availability.